Relevant physicochemical properties and metabolites with functional properties of two commercial varieties of Peruvian Pouteria lucuma - García-Ríos D. (2020)
Two commercial varieties of Peruvian Pouteria lucuma fruits namely “Seda” and “Beltrán” were characterized in terms of their physicochemical properties as well as their primary and secondary metabolites content and profile. Free sugars, dietary fiber, and starch comprise the main components in both varieties. Phenolic compounds derived from flavanoids (flavan-3-ols), gallic acid, and their derivatives were identified. Xanthophylls were tentatively identified based on their UV-vis spectra and enclosed the majority of the carotenoids found in lucuma. Additionally, both varieties showed to be sources of lipophilic compounds such as tocopherols (?, ?, and ?) and triterpenoids. The triterpenoid ?-amyrin was identified in a Pouteria fruit for the first time. The in vitro antioxidant capacity (AoxC) of the lipophilic fraction represented approximately 30% of the total AoxC. These results show that both lucuma varieties are rich sources of compounds with technological and functional properties with potential application in the food industry. Practical applications: Lucuma is a characteristic Peruvian fruit. To date, it is mainly used by the regional ice cream industry and it has been included recently in some confectionery products. Due to its high dietary fiber, carotenoids and sugar content it could be used as an alternative to the use of refined sugars and artificial colorants in the dairy and bakery industry. © 2020 Wiley Periodicals LLC.